Sectoral money demand and the great disinflation in the US - Alessandro Calza; Andrea Zaghini (European Central Bank (ECB), 2010)
Estimates of the welfare costs of inflation based on Bailey (1956) are typically computed using aggregate money demand models. Yet, the behavior of money demand may vary across sectors. Thus, the impact on welfare of inflation regime shifts may differ between households and firms. We specifically investigate the sectoral welfare implications of the shift from the Great Inflation to the present regime of low and stable inflation. For this purpose, we estimate different functional specifications of money demand for US households and non-financial firms using flow-of-fund data covering four decades. We find that the benefits were significant for both sectors.
Keywords: E31; E41; 330; ow of funds data; demand for money; welfare cost of ination; Inflationsrate; Preisstabilität; Soziale Kosten; Geldnachfrage; USA